A restatement of the natural science evidence base relevant to the control of bovine tuberculosis in Great Britain - Godfray,HCJ; Donnelly,CA; Kao,RR; Macdonald,W; McDonald,RA; Petrokofsky,G; Wood,JLN; Woodroffe,R; Young,DB; McLean,AR (Proceedings of the Royal Society B: Biological Sciences, 2013)
Bovine tuberculosis (bTB) is a very important disease of cattle in Great Britain, where it has been increasing in incidence and geographical distribution. In addition to cattle, it infects other species of domestic and wild animals, in particular the European badger (Meles meles). Policy to control bTB is vigorously debated and contentious because of its implications for the livestock industry and because some policy options involve culling badgers, the most important wildlife reservoir. This paper describes a project to provide a succinct summary of the natural science evidence base relevant to the control of bTB, couched in terms that are as policy-neutral as possible. Each evidence statement is placed into one of four categories describing the nature of the underlying information. The evidence summary forms the appendix to this paper and an annotated bibliography is provided in the electronic supplementary material.